Comparative Study on Postoperative Recovery Profiles of Desflurane and Sevoflurane Using I-GEL in Elective Ambulatory Surgeries - Paul, Suprotik; Saikia, Mousumi; Nayak, Sushil Kumar; Dutta, Swarup; Biswas, Chaitali (Journal of College of Medical Sciences-Nepal, 2023)
Introduction: In providing general anesthesia for ambulatory surgery, the goal is to achieve optimal surgical conditions while ensuring a rapid early recovery without side effects. Desflurane and sevoflurane are proven as effective ambulatory inhalational anesthetic agents. The aim of this research is to investigate and compared the hemodynamic stability, postoperative outcome and airway responses in elective ambulatory surgeries in patients receiving anesthesia with desflurane or sevoflurane using I-Gel supraglottic airway. Methods: A prospective, observational study was conducted involving 60 patients of age 18 – 50 years undergoing ambulatory surgeries under general anesthesia, randomly allocated into 2 equal groups receiving desflurane (Group D) or sevoflurane (Group S) for maintenance of anesthesia with suitable size I-Gel. Patients were monitored for hemodynamic parameters and postoperative recovery profile using fast track criteria (FTC) score at different time intervals. Pearson’s Chi Square test and Mann- Whitney U test were used for statistical analysis. Results: The mean time taken for postoperative recovery characteristics were significantly lower in Group D than Group S (p<0.001).The FTC score was significantly higher (p<0.001) in Group D than Group S at all-time intervals for 30 minutes. The requirement of additional analgesics was 46.7% in Group D and 60% in Group S (p>0.301) and that of antiemetic was 30% in Group D and 26.67% in Group S (p>0.774). Conclusions: Desflurane showed superior postoperative recovery characteristics and better FTC score without any increase in adverse airway events than sevoflurane.